The design of high lift aircraft configurations through multi-objective optimisation - Trapani, Giuseppe (Cranfield University, 2014)
An approach is proposed in this work to support the preliminary design of High-Lift aircraft configurations through the use of Multi-Objective optimisation tech¬niques. For this purpose a framework is developed which collates a Free-Form De¬formation parametrisation technique, a number of Computational Fluid Dynamics suites of different fidelity levels, a rapid aero-structure coupling procedure and two multi-objective optimisation techniques, namely Multi-Objective Tabu Search and Non-dominated Sorting Genetic Algorithm-II. The proposed optimisation framework is used for the execution of several design studies. Firstly, the deployment settings and elements' shape of the 2D multi-element GARTEUR A310 test case are optimised for take-off conditions. Consider¬able performance improvements are achieved using both the optimisation algorithms, though the sensitivity of the optimum designs to changes in operating conditions is highlighted. Therefore, a new optimisation set-up is proposed which successfully identifies operational robust designs. Secondly, the framework is extended to the optimisation of 3D geometries, using a Quasi-three-dimensional approach for the evaluation of the aerodynamic performance. The application to the deployment settings optimisation of the (DLF F11) KH3Y configuration illustrates that the method can be applied to more complicated real-world design cases. In particular, the deployment settings of slat and flaps (inboard and outboard segments) are suc¬cessfully optimised for landing conditions. Finally, a rapid aero-structure coupling procedure is implemented, in order to perform static aero-elastic analysis within the optimisation process. The KH3Y optimisation study is repeated including, this time, the effects of structural deformations. Different optima deployment settings are identified compared to the rigid case, illustrating that, despite being of reduced magnitude, wing deformations influence the optimum high-lift system settings. Furthermore, an industrial development and application of multi-objective opti-misation techniques is also presented. In the proposed approach, a reduced order model based on Proper Orthogonal Decomposition methods is used in an offline-online optimisation strategy. The results of the optimisation process for the RAE2822 single-element aerofoil and for the GARTEUR A310 multi-element aerofoil illustrate the potential of the method, as well as its limitations. The technical analysis is com-pleted with a description of the Agile project management approach used to run the project. Finally, future work directions have been identified and recommended.